2010
DOI: 10.1182/asheducation-2010.1.385
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Mini-Review: Is Indium-Labeled Autologous Platelet Scanning Predictive of Response to Splenectomy in Patients With Chronic Immune Thrombocytopenia?

Abstract: Clinical scenario: An otherwise healthy 25-year-old woman returns to your office for management of chronic primary immune thrombocytopenia. She was diagnosed 6 months earlier and continues to require prednisone 15 mg daily and periodic infusions of intravenous immunoglobulin to maintain a hemostatic platelet count. You discuss second-line treatment options, including splenectomy. The patient asks if there are any means by which to predict likelihood of response to splenectomy. You have heard about the use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…In this regard, other prognostic parameters should be explored before splenectomy, particularly radio-labeled platelet scans. 23,24 The analysis of the 95 patients (41%) who did not achieve a stable response showed that, despite most of them needing multiple lines of further treatments, a new response was achieved in 83% of the cases, confirming that splenectomy can convert refractory patients into responding ones, and does not exclude the possibility of a second response in relapsing patients. 19,20 Indeed, only 16 patients (7%) did not respond to any further treatment and only 3 (1%) died of bleeding complications.…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, other prognostic parameters should be explored before splenectomy, particularly radio-labeled platelet scans. 23,24 The analysis of the 95 patients (41%) who did not achieve a stable response showed that, despite most of them needing multiple lines of further treatments, a new response was achieved in 83% of the cases, confirming that splenectomy can convert refractory patients into responding ones, and does not exclude the possibility of a second response in relapsing patients. 19,20 Indeed, only 16 patients (7%) did not respond to any further treatment and only 3 (1%) died of bleeding complications.…”
Section: Discussionmentioning
confidence: 96%
“…Before considering splenectomy, we must evaluate comorbidities and life expectancy, and we usually perform an isotopic platelet lifespan study even though the value of platelet scan is debatable and its availability limited (Cuker & Cines, 2010). The number of patients reluctant to undergo splenectomy is increasing (Michel et al, 2015a) but predominant destruction of platelets in the spleen could be a strong argument for splenectomy, mainly in a 65-year-old patient with no co-morbidities and favourable ASA status.…”
Section: Life Expectancy and Cognitive Performancementioning
confidence: 99%
“…Recommendations would be influenced by the results of platelet isotopic distribution studies (if confirmed and if available). 51 At the other end of the spectrum, we try to avoid splenectomy in patients over 65-70 years of age (depending on their physical condition) not only because of higher complication rates but also because of lower response rates. The same considerations apply to the very frail, those with significant surgical comorbidities, history or risk of thrombosis, those with obligatory exposure to malaria or babesia, or those who have secondary ITP.…”
Section: Deciding Which Option To Pursuementioning
confidence: 99%